Feasibility Study of Smart Campus as Downscaled Smart City - Sanik, Mohd Erwan; Zulkifli, Nur Maghfirah; Hussin, Fatin Nur Izzati; Mohd Haekal, Nur Shafiqah (Multidisciplinary Applied Research and Innovation, 2021)
: Smart city is the combination of “smart city” and “digital city” concept where can integrates information and communication technology and various physical devices connected to the Internet of Things network and optimize the efficiency of city operations and services to connect with citizens. In Malaysia, people were lack of exposure to the smart city concept especially people in rural and suburban areas as well as students in various levels because it is not well introduced yet. Therefore, this study was carried out to produce feasibility study of smart campus as a downscaled of smart city. Google Form questionnaire was distributed to 384 respondents among students from various universities. Smart elements such as smart parking system, smart streetlight system, smart waste management, smart system for indoor environmental quality, smart bus management, smart security and safety, and smart campus living and learning are taken into consideration in the questionnaire. The research significance of this project is to identify understanding level of smart city concept among students. Moreover, it also study about suitability of smart campus during pandemic Covid-19 and the implementation of smart campus at UTHM Pagoh. The questionnaire consists of respondents’ demographic, understanding level on smart campus and smart city with and without assisted video, important of smart campus characteristic and use of smart matric card, implementation of smart campus and smart city during Covid-19 and application of smart campus on UTHM Pagoh. The result shows that respondents’ understanding was at medium level and significantly improved after watching the given informative video. Respondents also strongly agree on the statement of implementation of smart campus during pandemic Covid-19 because it have many benefits as it continued the teaching and learning process.